HASSKARL'S CINCHONA BARKS 1. HISTORICAL REVIEW - C. E. RIDSDALE; L. A. Anderson; A. T. Keene; J. I). Phi (BRIN Publishing (Penerbit BRIN), 1984)
The preliminary results of alkaloid analyses of Hasskaii's cinchona bark collection, made in Peru in 1852/3' is given, and the identity and historical aspects of the material discussed in respect of the role the plants played in the Javanese plantations.